Methodological approach as a strategy for professional employees' training in small and medium sized enterprises in Russia - Natalia L. Ivanova; Natalia V. Ippolitova; Irina N. Odarich (OmniaScience, 2019)
In the era of rapid development and the emergence of new methods and ideas for the employees' training in small and medium sized enterprises in Russia, managers need to think about the role that the methodological organization of the educational process, which refers, not only with respect to vocational training, but also in providing the methodological foundation for teaching certain disciplines in small and medium sized enterprises in Russia. The article describes the integrative-praxicological approach in the professional training of employees, it describes the principles and requirements as a methodological basis for the educational process.